MOHAMMAD NATSIR: SOME ASPECTS OF HIS THOUGHT ON STATEHOOD - Ma'mur, Ilzamuddin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 1996)
Mohammad Natsir: Some Aspects of His Thought on Statehood